Genetic Diversity, Association, and Path Coefficient Analyses of Sorghum [Sorghum bicolor (L.) Monech] Genotypes - Wedajo Gebre; Firew Mekbib; Alemu Tirfessa; Agdew Bekele (Scientifica)
For sustainable genetic improvement of crops like sorghum, assessing genetic variability and knowing the nature and extent of the association between grain yield and yield-related traits is a prerequisite. However, there needs to be sufficient information about the genetic variability study as well as yield-related trait correlation and path coefficient analysis for sorghum accessions, especially those from southern Ethiopia. Hence, this field experiment assessed genetic variability, determined the nature and extent of phenotypic–genetic correlation, and analyzed the path coefficients among 17 quantitative traits. A total of 225 sorghum genotypes were tested using a simple lattice design with two replications at the Jinka Agricultural Research Center during the 2021 cropping season. Based on the analysis of variance, most traits showed highly significant (P 0.001) differences, suggesting genetic diversity between the genotypes. High estimates of GCV and PCV were noted for leaf width (3924.50% and 3924.50%), while the lowest GCV and PCV estimates were obtained for days to flowering and days to maturity. High heritability coupled with high GAM estimates was recorded for plant height, leaf number, leaf length, leaf width, and leaf area. The magnitudes of genotypic correlations were higher than those of phenotypic correlations for most of the studied traits, implying that the traits under study were genetically controlled. Grain yield was positively and significantly correlated with most of the traits at phenotypic and genotypic levels, indicating the presence of a strong inherent association between grain yield and other traits. Phenotypic path coefficient analysis showed that grain filling period and biomass yield exerted a high positive direct effect on grain yield. Genotypic path coefficient analysis revealed that biomass yield, grain filling period, leaf width, and days to flowering had a relatively high positive direct effect on grain yield. However, days to maturity, plant height, leaf number, leaf area, yield per panicle, straw weight, and harvest index exerted a negative direct effect on grain yield. Almost for all the studied traits, genotypic direct and indirect effects were higher than the phenotypic direct and indirect effects, indicating that the studied traits had a genetically inherited relationship with grain yield. Grain yield in sorghum can be improved through indirect selection for traits such as plant height, leaf number, leaf length, leaf width, and biomass yield. In general, the observed variability and the information obtained from this study can be used for the genetic enhancement of sorghum thereby developing high-yielding varieties.